Effects of height and overactivation on a composite nickel-titanium T-loop - Ribeiro, Alexandre; Martins, Lidia [UNESP]; Junior, Roberto Silva [UNESP]; White, Larry; Martins, Renato [UNESP] (Elsevier, 2017)
Objective Evaluate the effect of height and overactivation on the force system produced by composite nickel-titanium T-loops. Material and Methods Forty nickel-titanium/stainless steel (SS) T-loops were divided into four groups according to height (7 or 6 mm) and activation/deactivation protocol (7 mm or 7 mm with 2 mm of overactivation). An Orthodontic Force Tester recorded the y-axis force and the x-axis moment produced for each 0.5 mm of deactivation, while the moment(x)-to-force(y) (M/F) ratio was calculated. The data were analyzed by three analyses of variance of repeated measures to detect differences and interactions between height and protocol on the three variables. Results T-loops with a height of 6 mm produced higher forces (2.97 N vs. 2.66 N) than those of 7 mm. The moments were similar, whereas the M/F was larger for the 7-mm loops (5.76 mm vs. 4.92 mm). The conventional activation produced higher forces (2.99 N vs. 2.64 N), higher moments (16.2 Nmm vs. 13.59 Nmm) but the same M/F. The M/F showed an interaction with deactivation. Conclusion The 6-mm-high T-loops produced higher forces, but lower M/F. The conventional protocol produced higher forces and moments. The M/F ratio was similar for both protocols, but overactivation produced a nearly constant M/F throughout deactivation. The use of a 7-mm-high overactivated segmented nickel-titanium loop might improve the performance of orthodontic space closure.
Keywords: Alloys; Loops; Nickel-titanium; Space Closure